A Comparative Case Study of Match-Fixing Laws in Singapore, Australia, Germany, and Switzerland. Issue 2 (3rd December 2022) - Hessert, Björn; Goh, Chui Ling
Abstract: Despite being ranked top three countries in the world in the Corruption Perception Index 2018, Singapore has a reputation in sports integrity for being the 'academy of match-fixers' in football and home to the leader of 'the world's most notorious match-fixing syndicate'. It is curious (and somewhat ironic) that Singapore, as one of the world's leaders in managing public section corruption, has been home to sports corruption and match-fixing locally and internationally. To date, Singapore has not instituted sport-specific laws on match-fixing to specifically combat match-fixing and other forms of manipulation of sports competitions in the country, and primarily relies on its criminal laws on corruption to prosecute match-fixing conduct, pursuant to the Prevention of Corruption Act (Cap 241, 1993 Rev Ed Singapore). This is in comparison to other countries which are home to match-fixing conduct, such as Australia, Germany, and Switzerland. This article will focus on the discussion on whether it is necessary for countries, with particular focus on Singapore, to enact sport-specific laws on match-fixing in their endeavour to combat match-fixing in their country. This work will conclude that while there are benefits to enacting sport-specific match-fixing laws, there may not be a dire or urgent need for Singapore to enact sport-specific laws on match-fixing. In any event, it may be necessary for Singapore authorities and sport governing bodies to take certain concrete steps to buttress the present regulation of match-fixing and state of players' contracts in order to mitigate the risks of such sports manipulation activities. One of these steps may include for Singapore to become a Signatory to the Council of Europe Convention on the Manipulation of Sports Competition (Macolin Convention).